Peaceful coexistence in light of the theories of Herbert Mead and Jürgen Habermas: A sociological reading - صابر, نيان نامق; رشيد, شيرين ابراهيم محمد (Sulaimani Journal for Humanities, 2019)
This study is concerned with the Study of Social theories of peaceful coexistence. There is no doubt that peaceful coexistence is important in multi-national, religious, doctrinal and Cultural Societies. The variety, Multiplicity, and deference is a reality in most societies. It’s normally that other societies marked by variety, multiple and difference. In order to be consciously aware with problems posed by this variety, Social theories should be relied upon as a basic way to avoid the danger of conflict and intolerance. Coexistence and recognition of the other produces a state of Dialogue and communication between individual and facilitate their meeting rather than their collision. Sociology is rich in many important theories that can be used in many important fields of life, the theories of Herbert Med & Jürgen Habermas can be considered as the most important theories in the field of peaceful Coexistence in societies.